2020
DOI: 10.1530/eje-20-0474
|View full text |Cite
|
Sign up to set email alerts
|

Rare CNVs provide novel insights into the molecular basis of GH and IGF-1 insensitivity

Abstract: Objective: Copy number variation (CNV) has been associated with idiopathic short stature, small for gestational age and Silver-Russell syndrome (SRS). It has not been extensively investigated in growth hormone insensitivity (GHI; short stature, IGF-1 deficiency and normal/high GH) or previously in IGF-1 insensitivity (short stature, high/normal GH and IGF-1). Design and Methods: Array Comparative Genomic Hybridisation was performed with ~60,000 probe oligonucleotide array in GHI (n=53) and IGF-1 insensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…The first cases of microscopic deletions in 1q21 have been published by Spengler et al [ 8 ] (Table 1 a, Fig. 1 a), and meanwhile four further cases with such alterations have been identified by molecular karyotyping in suspected SRS patients [ 9 , 10 ]. Furthermore, genomic alterations of the PLAG1 gene in 8q12.1 have recently been identified in patients with an SRS phenotype, including both SNVs [ 4 6 , 11 ] and CNVs [ 12 , 13 ] (Table 1 b, Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first cases of microscopic deletions in 1q21 have been published by Spengler et al [ 8 ] (Table 1 a, Fig. 1 a), and meanwhile four further cases with such alterations have been identified by molecular karyotyping in suspected SRS patients [ 9 , 10 ]. Furthermore, genomic alterations of the PLAG1 gene in 8q12.1 have recently been identified in patients with an SRS phenotype, including both SNVs [ 4 6 , 11 ] and CNVs [ 12 , 13 ] (Table 1 b, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in several public databases (DECIPHER, ClinVar), further cases with deletions affecting these regions are documented, but none of them exhibited alterations of similar size. Nearly all patients have been referred for molecular karyotyping due to clinical features of SRS, but only the NHS criteria are shown here Symptoms Our case [ 9 ] [ 8 ] SR9116 [ 8 ] SR5695 [ 10 ] patient 1a [ 10 ] patient 1b [ 10 ] patient 2 Frequency a Information on 1q21.1q21.2 cases Variant Affected 1q21.1q21.2 region (GRCh37) 145,895,747–147,897,962 145,261,451–148,343,412 145,770,626–147,831,171 145,932,455–147,831,171 146,564,742–147,735,011 146,641,600–147,735,011 145,987,155–147,735,011 Size of the deletion 2 Mb 3 Mb 2 Mb 1.9 Mb 1.17 Mb 1.09 Mb 1.74 Mb Parental origin de novo de novo maternal not maternal maternal maternal de novo NH-CSS criteria SGA/IUGR 0 0 1 1 NA NA NA 50.0% (2/4) Height at 2 years (< -2 SD) 0 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other subjects had a 5q12 deletion (Class 3), Xq26 deletion (Class 4), duplication of chromosome 10, a combination of 7q21 (Class 3) and 7q31 (Class 4) deletions, combined (Class 3) 7q21 and Xp22 duplication, 7q36 duplication (Class 3) and combined 3p22 deletion (Class 3), and combined 15q13 (Class 4) duplication and 3p22 (Class 3) deletion. Nine of these CNVs are described in our recent publication ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Growth hormone can also promote growth and development by forming a ternary complex with IGF-1 and IGFBP-3. 20 Indeed, a study on 50 patients with growth hormone deficiency showed that IGF-I and IGFBP-3 were highly sensitive and specific for diagnosing GHD. 21 In our study, IGF-1 and IGFBP-3 levels were higher in the high-dose group, indicating that exogenous rhGH supplementation can promote physical development through elevating these two hormones.…”
Section: Discussionmentioning
confidence: 99%